Increasing Production Capacity and Management of Palm Sugar Producing In MSME Purwabakti Village - Aditya Prima Yudha; Doni Wihartika; Dino Sukma; Mohamad Zikri (International Journal Of Community Service, 2026)
It was recorded that in 2023, there were 29.3 million MSMEs in Indonesia in the agriculture and fisheries sectors. One of the processed agricultural products in Indonesia is palm sugar. Palm sugar is a processed product that utilizes the sap of the sugar palm tree. Palm sugar can be a substitute for granulated sugar for diabetics. Researchers from the Center for Behavioral and Circular Economics Research (PR EPS) of the Indonesian Agency for Research on Indonesian National Agency for Research (BRIN) revealed that domestic production capacity is still far from sufficient to meet domestic market demand, let alone the export market. Purwabakti Village, located in Bogor Regency, has the potential to produce palm sugar. Palm sap or palm trees are abundant in this area. Palm sugar production is still relatively low. The amount of palm sugar produced by MSMEs in Purwabakti Village only ranges from 3-6 kg per week. Given the existing potential, palm sugar production can be increased. Production and marketing activities are still very conventional. Limited production facilities and production equipment are among the causes. In addition, palm sugar MSMEs face limitations in product distribution because they do not yet have a product brand and have not marketed through digital media. The Community Service Team provided training related to branding strategies, social media marketing, and the development of standard operating procedures (SOPs) for palm sugar production in Purwabakti Village. The activity resulted in the successful formulation of a brand for the Purwabakti village palm sugar product, namely "Manira Palm Sugar," and an Instagram social media account, "Manira Palm Sugar." The Community Service Team also developed a production standard operating procedure (SOP) that will serve as a standard for consistently producing quality palm sugar products.